Peningkatan Kemampuan Guru dalam Menyusun Kelengkapan Mengajar Melalui In-House Training pada SMK Negeri 1 Putussibau - Chr Marceiny, S.Pd (JARDIKNAS - Jurnal Pendidikan dan Sosial, 2021)
The purpose of this study was to improve the ability of teachers of SMK Negeri 1 Putussibau in compiling teaching equipment and to determine the right steps to improve the ability of teachers in compiling teaching equipment. With In-House Training it is expected that all teachers have sufficient knowledge, understanding and experience, especially in the preparation of teaching equipment which includes the Annual Program (Prota), Semester Program (Promes) and Learning Implementation Plan (RPP) in addition to other supporting equipment such as syllabus, educational calendar. , teaching schedules and student grade lists. The research was conducted in 2 cycles. In cycle 1, it was found that 58.23% of teachers successfully completed the preparation of teaching completeness and in Cycle 2 there were 91.66% of teachers who succeeded in completing the preparation of teaching completeness. So there is an increase in the ability of teachers in compiling teaching completeness after stage 1 of In-House Training is carried out, which is 33.43% and each teacher shows a significant increase